#### Question

Simplify the following expressions:

`(5 + sqrt7)(5 - sqrt7)`

#### Solution

We know that `(a + b)(a - b) = a^2 - b^2`We will use this property to simplify the expression

`(5 + sqrt7)(5 - sqrt7)`

`:. (5 + sqrt7)(5 - sqrt7) = 5^2 - (sqrt7)^2`

`= 5 xx 5 - sqrt7 xx sqrt7`

`25 - sqrt(7 xx 7)`

`= 25 - (7^2)^(1/2)`

`= 25 - 7^1`

= 18

Hence the value of expression is 18.

Is there an error in this question or solution?

Solution Simplify the Following Expressions: (5 + Sqrt7)(5 - Sqrt7) Concept: Operations on Real Numbers.